Participação do receptor metabotrópico de glutamato 5 na fisiologia de comportamentos motores e nas alterações motoras que ocorrem em camundongos modelo da doença de Huntington - Isabella Monteiro Guimaraes (2014)
Introduction: Huntington's disease (HD) is a neurodegenerative disorder, progressive and hereditary, that evolves inevitably to death. As we and others have demonstrated that the metabotropic glutamate receptor 5 (mGluR5) may have a role in HD pathology and that mGluR5 is involved in hyperkinetic movements, we decided to investigate whether mGluR5 has a role in HD-related hyperkinesia. Results: The results obtained in our study demonstrate that mGluR5 stimulation interferes in locomotor activity by acting on specific neural substrates. To determine mGluR5 role in HD, we have crossed HdhQ20/Q20and HdhQ111/Q111 mice with mGluR5 knockout mice (mGluR5-/-). mGluR5 knockout alters HD mice locomotor activity, indicating that there is a functional interaction between mutant Htt and mGluR5. To investigate the underlying changes in this locomotion regulation, a microarray assay was performed. The expression of a number of genes involved in movement control, such as dynein light chain and heavy chain and dynactin, were modified in a mouse model of HD lacking the expression of mGluR5 (HdhQ111/Q111/mGluR5-/-), as compared to its control HdhQ20/Q20/mGluR5-/-. These expression changes were confirmed by qPCR. Conclusion: The results indicate that mGluR5 plays a role in movement control by acting on specific neural substrates and that the receptor is likely involved in HD hyperkinesia. Moreover, our microarray data suggest that the mGluR5-related movement alterations observed in the HD mouse model might be due to modifications in the expression of genes that codify for movement control related proteins.